Formal aspects of security and trust 7th International Workshop, FAST 2010, Pisa, Italy, September 16-17, 2010. Revised Selected Papers - FAST (Workshop) 2010 Pisa, Italy); Degano, Pierpaolo; Etalle, Sandro; Guttman, Joshua; SpringerLink (Online service). (Berlin Heidelberg Springer, 2011)
This book constitutes the thoroughly refereed post-proceedings of the 7th International Workshop on Formal Aspects of Security and Trust, FAST 2010, held as part of the 8th IEEE International Conference on Software Engineering and Formal Methods, SEFM 2010 in Pisa, Italy in September 2010. The 14 revised full papers presented together with one invited paper were carefully reviewed and selected from 42 submissions. The papers focus of formal aspects in security and trust policy models, security protocol design and analysis, formal models of trust and reputation, logics for security and trust, distributed trust management systems, trust-based reasoning, digital assets protection, data protection, privacy and id issues, information flow analysis, language-based security, security and trust aspects in ubiquitous computing, validation/analysis tools, web service security/trust/privacy, grid security, security risk assessment, and case studies.
Electronic reproduction.
Keywords: Formal methods (Computer science) -- Congresses; Computer security -- Congresses; Electronic books